Occurrence and prevention of novel coronavirus pneumonia from the theory of plague - MA Ya-hui, MA Shi-cai, LIAN Jian-wei, ZHENG Hong (Jichu yixue yu linchuang, 2020)
Starting from the related theory of plague, this thesis reveals the relationship between plague and novel coronavirus pneumonia, it also provides integrated Chinese and western medicine treatment ideas for the occurrence and defense of 2019-nCoV pneumonia. According to the characteristics of this disease, it can be classified in the category of “plague” in Traditional Chinese Medicine (TCM). This thesis expounds the meaning and development of the plague, discusses the stage differentiation and treatment of 2019-nCoV from view of TCM. New insights into the occurrence, treatment and defense of 2019-nCoV pneumonia are helpful to cure patients with 2019- nCoV pneumonia more effectively.